Comparative Genomics of Glossina palpalis gambiensis and G. morsitans morsitans to Reveal Gene Orthologs Involved in Infection by Trypanosoma brucei gambiense - Hamidou Soumana, Illiassou; Tchicaya, Bernadette; Rialle, Stéphanie; Parrinello, Hugues; Geiger, Anne (Frontiers in Microbiology, 2017)
Blood-feeding Glossina palpalis gambiense (Gpg) fly transmits the single-celled eukaryotic parasite Trypanosoma brucei gambiense (Tbg), the second Glossina fly African trypanosome pair being Glossina morsitans / T. brucei rhodesiense. Whatever the T. brucei subspecies, whereas the onset of their developmental program in the zoo-anthropophilic blood feeding flies does unfold in the fly midgut, its completion is taking place in the fly salivary gland where does emerge a low size metacyclic trypomastigote population displaying features that account for its establishment in mammals-human individuals included. Considering that the two Glossina - T. brucei pairs introduced above share similarity with respect to the developmental program of this African parasite, we were curious to map on the Glossina morsitans morsitans (Gmm), the Differentially Expressed Genes (DEGs) we listed in a previous study. Briefly, using the gut samples collected at days 3, 10 and 20, from Gpg that were fed or not at day 0 on Tbg - hosting mice, these DGE lists were obtained from RNA seq - based approaches. Here post the mapping on the quality controlled DEGs on the Gmm genome, the identified ortholog genes were further annotated, the resulting datasets being compared. Around 50% of the Gpg DEGs were shown to have orthologs in the Gmm genome. Under one of the three Glossina midgut sampling conditions, the number of DEGs was even higher when mapping on the Gmm genome than initially recorded. Many Gmm genes annotated as “Hypothetical” were mapped and annotated on many distinct databases allowing some of them to be properly identified. We identify Glossina fly candidate genes encoding (a) a broad panel of proteases as well as (b) chitin - binding proteins, (c) antimicrobial peptide production - Pro3 protein, transferrin, mucin, atttacin, cecropin, etc - to further select in functional studies, the objectives being to probe and validated fly genome manipulation that prevents the onset of the developmental program of one or the other T. brucei spp stumpy form sampled by one of the other bloodfeeding Glossina subspecies.